Community College Models Globalization and Higher Education Reform - Latiner Raby, Rosalind; Valeau, Edward J. (Springer Netherlands : Imprint: Springer, 2009)
Increasingly, students worldwide are seeking post-secondary education to acquire new skill-sets and credentials. There is an explosion of community college models that provide educational opportunities and alternative pathways for students who do not fit the traditional higher educational profile. This book focuses on economic models to help local and national economies develop strong workforce training, humanitarian models to bring about social mobility and peace, transformative models to help institutions expand and keep up with societal needs, and newly created models that respond to the educational and training needs of a constantly changing world. These models seek to capture the imagination of those who are committed to learning about what works in higher education and in particular, the impact community college models are having on the changing nature of world social, political and economic landscapes. With contributors representing 30 countries, this book presents an international perspective.